A novel bio‐active adhesive monomer induces odontoblast differentiation: a comparative study. (30th July 2020) - Qiu, Y. J.; Tang, J.; Saito, T.
Abstract: Aim: To evaluate the in vitro effect of the novel adhesive monomer CMET, a calcium salt of 4‐methacryloxyethyl trimellitate (4‐MET), on the proliferation, mineralization and differentiation of odontoblast‐like cells, comparing with 4‐MET, calcium hydroxide (CH) and mineral trioxide aggregate (MTA). Methodology: Rat odontoblast‐like MDPC‐23 cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 5% foetal bovine serum. The powder of four tested materials (CMET, 4‐MET, CH and MTA) was first dissolved in distilled water (dH2 O) and then was diluted by DMEM to yield final concentrations. Solvent (dH2 O) was used as a control. Cell viability was assessed using CCK‐8 assay. Real‐time RT‐PCR was used to quantify the mRNA expression of odontogenic markers, cytokines and integrins. Mineralization inducing capacity was evaluated by alkaline phosphatase (ALPase) activity and alizarin red S staining. Statistical analyses were performed using one‐way anova and post hoc Tukey's HSD test, with the significance level at 1%. Results: Cell viability was significantly greater in the CMET‐ (83 to 828 mmol L −1 ), CH‐ and MTA‐treated (low concentrations) groups than that in the control group ( P < 0.01). Higher concentrations of each material decreased the viable cells to different extents ( P < 0.01). CMET treatment augmented the expression of several integrin subunits and exhibited the highest mRNA expression levels of odontogenic markers among all groups ( P < 0.01). CH and MTA treatment caused significantly greater upregulation of pro‐inflammatory cytokines expression than the other groups ( P < 0.01). The calcific deposition of MDPC‐23 cells was dose‐dependently accelerated by the addition of CMET ( P < 0.01); the enhancement of mineralization was also found in the fresh prepared CH and MTA treatments. Besides, CMET showed consistency in mineralization induction after 8 weeks storage. Exposure to SB202190, a specific p38 mitogen‐activated protein kinases inhibitor, significantly decreased the ALPase activity as well as the mineral deposition which was enhanced by CMET treatment ( P < 0.01). Conclusions: The novel bio‐active monomer had the lowest cytotoxicity among all groups and it induced the proliferation, mineralization and differentiation of odontoblast‐like cells under appropriate concentrations. This adhesive monomer possesses excellent biocompatibility and hence exhibits great potential in dentine regeneration.